Turkey’s Assistance to Iraq after 2014: Key Determinants and Components - A. I. Aliyeva (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the 2010s amid the destabilization of the region and the outbreak of new armed conﬂicts the inﬂuence of the Republic of Turkey in the Arab world has signiﬁcantly increased. The proclamation of the Islamic State in the neighbouring countries in the sphere of Turkey’s interest — Syria and Iraq — became a kind of watershed. And whereas Ankara’s strategy in Syria has received substantial attention of researchers, its policy towards Iraq which included both military and non-military measures remains understudied. The paper aims to uncover the logic behind Turkey’s assistance to Iraq to counter territorial expansion of the Islamic State and to remedy the negative impact of its presence. The paper is divided into two sections. The ﬁrst section focuses on the military-political interaction between the Republic of Turkey and Iraq after 2014. The second examines speciﬁcs of the Turkish non-military assistance to its neighbour. The author stresses that Ankara’s military support to Baghdad in the ﬁght against ‘ISIS’ included expansion of the Turkish troops’ presence in Iraq and escalation of tensions with the Kurdistan Workers’ Party. That has, in turn, led to the growing tension between Turkey and Iraq. As for the civilian assistance, Turkey has focused on its humanitarian dimension implementing relatively small projects — mainly in the areas populated by the Iraqi Turkomans. After declaring victory over the Islamic State, Ankara did not rush to increase the level of its grant assistance that remained relatively low. At the same time Turkey sought to create, particularly through tied loans, advantageous conditions to attract Turkish construction companies to the reconstruction of destroyed infrastructure in Iraq. Thus, the paper shows that during this internationalized internal conﬂict, as well as after its formal end, Turkey has tended to prioritize its national interests, aiming to strengthen its strategic and economic presence in the neighbouring country through a combination of military and non-military measures. However, a recent destabilization of the situation in Iraq poses new challenges to the Ankara’s strategy towards Iraq and highlights the need for further monitoring of the development of Turkish-Iraqi relations.